Beyond immigrant status: Book-sharing in low-income Mexican-American families. (March 2017) - Salinas, Maria; Pérez-Granados, Deanne R; Feldman, Heidi M; Huffman, Lynne C
Data from a sample (n = 145) of low-income Mexican-American mothers and their toddlers (9–26 months) were used to explore the prevalence of high-frequency book-sharing (⩾3 days/week) and its association with maternal immigrant status (Mexico-born vs US-born), as well as other demographic and psychosocial factors. Mexico-born mothers were more likely to report frequent book-sharing than were their US-born counterparts. This was contrary to expectations, and may be representative of the "immigrant paradox." Other variables associated with high-frequency book-sharing included not receiving welfare, low levels of parenting stress, and having 10 or more books in the home; these factors remained statistically significant in multivariate logistic regression models. The findings of this study have the potential to inform not only intervention efforts targeting emergent literacy in family contexts and children's school readiness in Latino families, but also practitioners and policy makers in the health and social services. Pediatricians and other health and social service practitioners are encouraged to be aware of the demographic and psychosocial factors that can affect mothers' pursuit of child-focused early literacy activities.